EXPLORATION OF CHEMICAL CONTENT AND ANTIBACTERIAL ACTIVITY OF SENDOK LEAVES (Plantago Major) USING AL-QUR'AN RECITATION THERAPY - Leni Legasari; Ana Maghpiroh; Muyasaroh Muyasaroh (UPT Publication and Journal Management, Islamic University of Kalimantan, 2024)
Treatment techniques using herbal remedies combined with Qur'anic verses are alternative treatment methods that have been practiced since the time of Prophet Muhammad. One of the medicinal plants used as a traditional herb is the sendok plant (Plantago major). Sendok leaves are known to have antibacterial properties that can be used to treat bacterial infections, especially amidst the challenges of bacterial resistance to synthetic antibiotics. The aim of this study is to explore the effect of spiritual methods on enhancing the therapeutic properties of Sendok leaves. After being treated with Qur'anic recitation, the leaves of the plant were analyzed for their chemical content, and bioactivity testing was carried out. The results showed a quantitative difference in the chemical compounds, as determined by GC-MS analysis. Antibacterial testing also revealed an increase in bioactivity, especially against Staphylococcus aureus bacteria, in the plants that received Qur'anic recitation treatment.